A topological semimetal Li2CrN2 sheet as a promising hydrogen storage material. Issue 22 (1st June 2020) - Ma, Li-Juan; Sun, Qiang
Abstract : The hydrogen storage performance of topological quantum materials is explored for the first time. Abstract : An ideal electrode for electrochemical storage of hydrogen needs to be conductive for electrons. The robust conductivity protected by topology in topological quantum materials just meets this requirement. However, such a study is still lacking so far. Herein, for the first time, we explore the performance of hydrogen storage in a topological quantum material Li2 CrN2 sheet, and have found that the interaction between H2 and the sheet is mainly attributed to the polarization mechanism, resulting in a gravimetric capacity of 4.77% that is higher than the value of the Li decorated MoS2 (4.4%), Li-decorated phosphorene (4.4%) and Li substituted BHNH sheet (3.16%). The hydrogen adsorption energy is found to be in the range of 0.16–0.33 eV, which is in the required energy window for balancing the adsorption stability and fast kinetics, and the releasing temperature is in the range of 160–270 K, desirable for practical operations. This study is of significance for fuel cell applications going beyond the conventional materials for hydrogen storage.